Memerkenalkan Sejarah Pahlawan Nasional Ki Sarmidi Mangunsarkoro bagi Peserta Didik MI/SD di Indonesia - septia indah cahyani; Anis Fuadah Z (el-Ibtidaiy:Journal of Primary Education, 2020)
Behind the independence of the Indonesian State, many things are behind it. Education in Indonesia has existed since ancient times, to be precise in the pre-literacy era. Its development started from the pre-script era, the Hindu-Buddhist kingdom, and Islam until today. Ki Sarmidi Mangunsarkoro is an important factor in the field of education in Indonesia. The Minister of Teaching, Education and Culture, which he occupied, made many changes in Indonesia. The establishment of the Jakarta branch of Taman Siswa made children around them grow interested in reading and provided schools for children from underprivileged families. This study aims to improve students' enthusiasm for learning and to have a sense of struggle for education in Indonesia. The method that can be done is by looking for information about the history of Ki Sarmidi Mangunsarkoro from the history books of the Minister and the Indonesian Cabinet as well as the history books of Ki Sarmidi Mangunsarkoro. The results of this study show that students have a high enthusiasm for learning so that they can continue to the tertiary level and education in Indonesia becomes more advanced. Students have the nature of the view that education is very important. With the history of Ki Sarmidi Mangunsarkoro, there are a lot of knowledge of attitudes and morals that can be taken, one of which is educational.